(untitled) (Rome, 1994)
This publication represents the second series. Agricultural policy analysts require better ways of tailoring and targeting policy instruments and agricultural programmes to the actual circumstances of farm-households and rural communities. The overall objective of this document is to improve agricultural polices and programmes though the better use of micro-level analytical methods. Common methods are compared and contrasted for the benefit of those who manage agricultural policy analysis in developing countries
Keywords: Agricultural development projects,Agricultural administration,Agriculture; Developing countries,Evaluation,Developing countries,Evaluation,Economic aspects,Developing countries